Dermatophagoides farinae microRNAs released to external environments via exosomes regulate inflammation-related gene expression in human bronchial epithelial cells - He, Kaiyue; Yang, Ting; Yu, Jinyan; Zang, Xiao; Jiang, Shangde; Xu, Shuyue; Liu, Jiaxi; Xu, Zuyu; Wang, Wei; Hong, Shanchao (Frontiers in Immunology, 2023)
Background: Dermatophagoides farinae (DFA) is an important species of house dust mites (HDMs) that causes allergic diseases. Previous studies have focused on allergens with protein components to explain the allergic effect of HDMs; however, there is little knowledge on the role of microRNAs (miRNAs) in the allergic effect of HDMs. This study aimed to unravel the new mechanism of dust mite sensitization from the perspective of cross-species transport of extracellular vesicles-encapsulated miRNAs from HDMs.Methods: Small RNA (sRNA) sequencing was performed to detected miRNAs expression profiles from DFA, DFA-derived exosomes and DFA culture supernatants.A quantitative fluorescent real-time PCR (qPCR) assay was used to detect miRNAs from HDMsexpression in dust specimens. BEAS-2B cells endocytosed exosomes were modeled in vitro to detect miRNAs from DFA and the expression of related inflammatory factors. Representative dfa-miR-276-3p and dfa-novel-miR2 were transfected into BEAS-2B cells, and then differentially expressed genes (DEGs) were analyzed by RNA sequencing. Protein-protein interaction (PPI) network analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) terms enrichment analyses were performed on the first 300 nodes of DEGs.Results: RNA sequencing identified 42 conserved miRNAs and 66 novel miRNAs in DFA, DFA-derived exosomes, and DFA culture supernatants. A homology analysis was performed on the top 18 conserved miRNAs with high expression levels. The presence of dust mites and miRNAs from HDMs in living environment were also validated. After Following uptake of DFA-derived exosomes from DFA by BEAS-2B cells, exosomes transported miRNAs from DFA to target cells and produced pro-inflammatory effects in corresponding cells. RNA sequencing revealed theidentified DEGs of in dfa-miR-276-3p and dfa-novel-miR2 transfected into BEAS-2B cells. GO and KEGG enrichment analyses revealed the role of exosomes with cross-species transporting of DFA miRNAs from DFA in inflammatory signaling pathways, such as JAK-STAT signaling pathway, PI3K/AKT signaling pathway and IL-6-mediated signaling pathway.Our findings demonstrate the miRNAs expression profiles of in DFA for the first time. The DFA miRNAs from DFA are delivered into living environments via exosomes, and engulfed by human bronchial epithelial cells, and cross-species regulation may contribute to inflammation-related processes.